The Influence Of Leadership And Discipline On The Performance Of Village Offices In South Seluma District Area Seluma Regency - Hamid, Darwan; Irwanto, Tito; Subhi, Ramadan (Utami Publisher, 2025)
Village officials play a crucial role in running the government at the village level. The success of village governance is inseparable from the performance of the village officials themselves. Good performance will be achieved if supported by effective leadership and high discipline from each village official. The purpose of this study was to determine the influence of leadership and discipline on the performance of village officials in the South Seluma District, Seluma Regency.The research objective used a quantitative method with a descriptive analysis approach. The analytical method in this study uses Validity Test, Reliability Test, Multiple Linear Analysis, Determination Coefficient, and Hypothesis Testing using T-Test, F-Test. The number of respondents was 30 people from all village officials in South Seluma District, which consists of four villages, namely Sengkuang Village, Tanjungan Village, Tanjung Seru Village, and Padang Genting Village.The results of multiple linear regression analysis obtained the equation: Y = 0.764 - 0.008X1 + 0.986X2 + e These results indicate that leadership (X₁) has a negative coefficient value (-0.008) and does not significantly influence the performance of village officials with a calculated t value of -0.046 <t table 1.703 and a significance of 0.986> 0.05. Meanwhile, discipline (X₂) has a positive and significant effect on the performance of village officials with a calculated t value of 5.944 > t table 1.703 and a significance of 0.000 < 0.05. The results of the simultaneous test (F test) show that leadership and discipline together have a significant effect on the performance of village officials with a calculated F value of 966.757 > F table 3.354 and a significance of 0.000 < 0.05. The Adjusted R² value of 0.985 means that 98.5% of the variation in village official performance is explained by leadership and discipline, while the remaining 1.5% is influenced by other factors outside this study.